Project to Strengthen Pancasila Student Profile as an Application of Differentiated Learning in the Independent Curriculum: A Case Study at a Senior High School in Pandeglang, Indonesia - Usman, Usman; Nuraulia, Dwi; Nauroh, Rahmi; Rajudin, Iin; Rifqiawati, Ika (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the implementation of project to strengthen Pancasila student profile activities as a project to strengthen the profile of Pancasila students at a senior high school in pandeglang district, indonesia, as well as the impact of its implementation on students. The procedure used in this study is a qualitative method with a descriptive approach. The data collection methods used are interviews and questionnaires. The interview was conducted with seven respondents, namely teachers at a senior high school in pandeglang district, indonesia, who are facilitators in implementing an independent curriculum in the classroom, as well as class X and XI students as participants in project to strengthen Pancasila student profile activities. Students are required to make or do a project to implement an independent curriculum. Project activities in this independent curriculum, one of which is by carrying out project to strengthen Pancasila student profile activities. The project to strengthen Pancasila student profile activity is a project to strengthen Pancasila students' profiles. The project to strengthen Pancasila student profile activities were adjusted to the seven themes arranged by the Indonesian Ministry of Education, Culture, Research, and Technology. The project results to be displayed in the project to strengthen Pancasila student profile project exhibition at a senior high school in pandeglang district, indonesia, include (1) Posters; (2) A bulletin board; (3) Democracy pocketbook; (4) A best practice anti-bullying. A senior high school in pandeglang district, indonesia, is included in the activator school with activator teachers, making differentiated learning a strategy in the activator teacher program activities.